Multiple Discrimination and the Quality of Jobs across Europe - Tardos, Katalin (Socio.hu Társadalomtudományi Szemle, 2013)
The paper investigates the phenomenon of multiple discrimination and the quality of jobs available on the labour market in the European Union. Numerous studies have demonstrated the negative impact of discrimination on employment prospects; however, only a very few have investigated how discrimination relates to overall job quality. The paper analyses the significance of discrimination on multiple grounds; the grounds of discrimination that are most likely to be combined, and finally, whether there is a significant difference in the employment rate and job quality among victims of single or multiple–grounds discrimination. The research tested the hypothesis that victims of multiple discrimination have both a lower employment rate and, when employed, a lower overall job quality compared to those affected by no or single–grounds discrimination at the same educational level. To measure the overall job quality of respondents, a complex index has been designed. The research evaluates data from the fifth round of the European Social Survey (ESS) conducted in 2010. The findings reinforced the view that victims of multiple discrimination had a lower jobquality level compared to those not discriminated against, or discriminated on a single ground, especially at the lower and higher ends of the educational continuum. Furthermore, the research revealed important methodological implications concerning the measurement of discrimination. KEYWORDS Multiple discrimination, job quality, social exclusion